Mediator difference in contractions between trachea and bronchus of guinea pig induced by stimulation of C-fibers in vitro - Fang Li-ben; Yang Qiu-huo; Bian Ru-lian (Acta Pharmacologica Sinica, 2016)
In trachea and bronchus of guinea pig in vitro, electric field stimulation (EFS) induced a rapid contraction (phase I) followed by a long-lasting contraction (phase II). The pretreatments of chlorphenamine (Chl) 1 mumol.L-1 and disodium cromoglycate (Cro) 10 mumol.L-1 reduced the tracheal contraction of phase II from 49 +/- 23 mg and 34 +/- 18 mg to 27 +/- 21 and 18 +/- 12 mg, respectively. The contractile responses of the tracheae to increasing concentrations of substance P (SP) 0.1-3.0 mumol.L-1 were reduced by the pretreatment of Cro 10 mumol.L-1 (P < 0.01). On the contrary, the contractile responses of the bronchi were not inhibited by Cro or Chl but were inhibited by pretreatment of atropine 1 mumol.L-1 from 61 +/- 36 mg to 36 +/- 15 mg. These results show that there are different mechanisms in the EFS-induced contractions between the trachea and bronchus; that different mediators amplify the phase II contractions.